2015
DOI: 10.1186/s40104-015-0001-8
|View full text |Cite
|
Sign up to set email alerts
|

Developmental programming: the role of growth hormone

Abstract: Developmental programming of the fetus has consequences for physiologic responses in the offspring as an adult and, more recently, is implicated in the expression of altered phenotypes of future generations. Some phenotypes, such as fertility, bone strength, and adiposity are highly relevant to food animal production and in utero factors that impinge on those traits are vital to understand. A key systemic regulatory hormone is growth hormone (GH), which has a developmental role in virtually all tissues and org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 95 publications
(105 reference statements)
1
21
0
1
Order By: Relevance
“…There is a body of evidence indicating that in utero exposure to maternal factors such as obesity, poor diet and smoking can modify gene expression though DNA methylation and histones, which can exacerbate obesity in later life [ 8 , 39 ]. It is now known that these epigenetic changes can be inherited, and their effects continue over several generations [ 40 ]. In principle, epigenetic effects may be harmful or protective.…”
Section: Discussionmentioning
confidence: 99%
“…There is a body of evidence indicating that in utero exposure to maternal factors such as obesity, poor diet and smoking can modify gene expression though DNA methylation and histones, which can exacerbate obesity in later life [ 8 , 39 ]. It is now known that these epigenetic changes can be inherited, and their effects continue over several generations [ 40 ]. In principle, epigenetic effects may be harmful or protective.…”
Section: Discussionmentioning
confidence: 99%
“…In both regions, we detected several haplotypes that are preferentially transmitted to one sex or the other, which is in concordance with the prediction of theoretical works (Úbeda and Haig 2005;Burt and Trivers 2006;Patten et al 2010;Ubeda et al 2011;Patten 2014). The chromosome 17 region encompasses the growth hormone locus, notably the GH gene, which encodes a protein in the placenta that is important for in utero development (Oberbauer 2015), and affects adult traits such as height and bone mineral density (Timasheva et al 2013). Interestingly, there is evidence for ongoing IASC on human height (Stulp et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the extended elevation of GH can disrupt the normal physiological response to hyperleptinemia [ 54 ], thus predisposing towards leptin resistance and obesity, with the most likely mechanism underpinning leptin signaling impairment being at the level of the ARC. It has been well-established that adverse developmental programming disrupts the normal wiring of the pathways that regulate energy balance via a disruption in neurite outgrowth in the ARC and changes in the expression of anorixigenic/orexigenic factors, including neuropeptide Y (NPY), proopiomelanocortin (POMC), and agouti-related peptide (AgRP).…”
Section: Animal Models Of Manipulation Of the Gh-igf Axismentioning
confidence: 99%